AC conductivity and ion dynamics of alkaline earth metal substituted Telluride glasses - Jha P.A.; Yadav A.K.; Jha P.K.; Singh P. (My University, 2025)
The Telluride based glass systems 0.70TeO2-0.30BaO (TB30) and 0.65TeO2-0.35BaO (TB35) were prepared by conventional melt quenching method. The structural studies were characterized by X-ray diffraction and Scanning Electron microscopy. The elemental composition has also been confirmed using Energy Dispersive X-ray analysis (EDAX). In the present report, ion dynamics of the glass systems has been studied using AC conductivity spectroscopy techniques. The measured conductivity data of these glass systems in the frequency range 20 Hz to 1 MHz at different temperatures were analyzed using Jonscher Power Law and Dyre's free energy barrier model. The conductivity and hopping frequency calculated through both models have been used to find the activation energy. The scaling behaviour of the two glass systems was studied using Ghosh and Dyre's scaling models. The conductivity spectra of TB30 were found to follow both the Ghosh and Dyre's scaling model whereas the conductivity spectra of TB35 were unable to follow both the scaling models. Moreover, the modulus spectra also showed the similar trend i.e. TB30 showed modulus scaling and TB35 failed to show scaled modulus spectra. The scaling behaviour showed temperature independent conduction mechanism in TB30. © 2016 Elsevier B.V.